2021
DOI: 10.3906/kim-2009-59
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterisation of Phlomis linearis Boiss. & Bal and screening for anticholinesterase, antiamylase, antimicrobial, and cytotoxic properties

Abstract: In the present work, essential oil and fatty acids and extracts obtained from aerial parts of Phlomis linearis Boiss. & Bal. were investigated for chemical composition and biological activities. The phytochemical analyses were conducted with gas chromatography-mass spectrometry/flame ionisation detector (GC-MS/FID) and liquid chromatography-mass spectromtetry (LC-MS/MS) techniques. The extracts and essential oil were studied for α -amylase and acetylcholinesterase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
1
0
1
Order By: Relevance
“…Plant extract showed effective anti-diabetic potential which might be attributed to the presence of sinapinic acid. In similar lines, our results are in agreement with previous reports that MPs of Phlomis species have a wide range of bioactive constituent which are responsible for antioxidants, anti-diabetic, anti-inflammatory, anti-microbial effects [40]. Liver, which is a vital metabolic organ, is involved in various biochemical processes of the body in maintaining homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…Plant extract showed effective anti-diabetic potential which might be attributed to the presence of sinapinic acid. In similar lines, our results are in agreement with previous reports that MPs of Phlomis species have a wide range of bioactive constituent which are responsible for antioxidants, anti-diabetic, anti-inflammatory, anti-microbial effects [40]. Liver, which is a vital metabolic organ, is involved in various biochemical processes of the body in maintaining homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the antimicrobial screening revealed that the MIC value of P. linearis was >500 mg/ml against all bacteria and yeast strains while the MIC value of antibiotics was 3.91 ->125 mg/ml (Table 1). Unlike our high MIC value results, Göger et al (2021) showed that the MIC value of P. linearis EtOAc extracts against S. aureus strain was 156.25 µg/ml, E. coli and C. albicans were 625 μg/ml indicating that the plant was resistant to the EtOAc extract but susceptible to the water extract of P. linearis. The different MIC values were attributed to the polarity of the solvent, different stages of growth, and the environment of the plant, which can significantly affect their chemical composition (Koutsoukis et al, 2019).…”
Section: Antimicrobial Activitycontrasting
confidence: 99%